ทรายอะราโกไนต์แปรรูปจากเปลือกหอยแมลงภู่ - ครรชิต ประทุมราช (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This independent research project aims to study the processing of Green mussel shells in the seafood industry by using innovation to create value for productivity. It is the original aragonite sand. To study the factors affecting the efficiency of processing aragonite sand from Green mussel shells. For use as a base material for marine aquariums. To study the business plan and commercial feasibility of the introduction of Green mussel shells in the seafood production industry to be transformed into valuable materials according to the concept Turn Waste to Wealth and Zero Waste Management as well as developing a prototype aragonite sand to replace the use of natural materials. To promote development guidelines for sustainability of the United Nations by using a practical model at every step since the Green mussel shells material is brought from the villagers who have a career in shellfish carving. Brought through the process tested in the laboratory of Chulalongkorn University until a prototype product comes out and uses a quantitative research model take a questionnaire to prove the factors affecting the accept the innovation of processed aragonite sand from Green mussel shells. Able to collect information that supports independent study approaches. Ready to bring useful information to support the next step of product development.